Demographic Responses of Akodon Azarae (Rodentia: Cricetidae) Enclosed Populations to Rogenhofera Bonaerensis Bot Fly Parasitism - Gelin Spessot, Maria Laura (2013)
. We assessed the effect of Rogenhofera bonaerensis parasitism on demographic parameters of Akodon azarae enclosure populations using CMR models. Survival (S), transition (Ψ) and encounter (p) probabilities were modelled using program MARK, restricted by time, sex, abundance and infection state (non-infected and infected individuals). A low rate of infection and a high recovery rate of infected individuals were observed. Survival only showed temporal variation with decreasing values by June. The parasitosis caused by the fly seems to have no influence on the demography of A. azarae populations. The observed pattern in demography of enclosure populations is in agreement with natural populations of this species.